The effects of soil structural formation on crop development - Wareosh, Mustafa (2019)
Soil structure is a key element in determining the plant available water content and nutrient availability. Therefore, it is essential to study the effects of environmental factors on soil structure formation (especially the effect of weathering at after sowing), The soil surface was examined following different treatments of surface coverage (e.g. duration) to study the changes in soil structure and seed emergence timings simultaneously. The early stage soil surface coverage enhanced the soil structure formation so that the root system could be readily established and distributed consuming minimum plant energy which led to significantly higher (P<0.05) plant shoot and yield. While the soil surface treatments that were exposed to weathering (control) had the lowest yield. Additionally, the early stage soil surface coverage produced more circular pores which led to a significantly higher (P<0.05) soil water content. The results showed that the early stage soil coverage treatments for the growing seasons 2014/2015 and 2015/2016 had the significantly higher (P<0.05) soil pore circularity, water content, root, shoot and yield than the control treatments. A second experiment sought to quantify the effects and role of roots in soil structure formation using there the same soil cover treatments previously employed on a trial cultivated with winter wheat (cv. Rialto). The results showed that the presence of roots significantly (P<0.05) boosted the soil physical parameters such as porosity, water content, soil pore circularity and soil mean pore size in comparison with bare soil.